KAJIAN FILOSOFIS NIBANNA DALAM KITAB SUTTA PITAKA - Made Sri Putri Purnamawati (Pangkaja: Jurnal Agama Hindu, 2022)
Buddhist philosophy does not teach that life goal can only be achieved in life in another realm. Herein lies the main difference between the Buddhist concept of Nibbana and the Non-Buddhist (Hindu) concept, Nibbana being freedom from suffering, the destruction of egoism, greed, hatred and delusion. Based on this description, the author is very interested in researching the Philosophical Study of Nibbana in the Sutta Pitaka. This type of research is a type of qualitative research. The data collection techniques in this study are; literature review, interviews, and documentation. In this study, the raw data that had been collected were processed using descriptive and qualitative methods. The concept of Nibbana in the Sutta Pitaka is a very unique Buddhist philosophy. Nibbana is something that cannot be described in words because Nibbana can only be understood by the wise. Nibbana is a definite state after craving disappears, fire is extinguished because it runs out of fuel as well as Nibbana is the cessation of craving, attachment, passions and defilements. Nibbana is the Eternal Truth, unborn, unperishable and unchanging. The philosophical study of Nibbana in the Sutta Pitaka includes the study of Ontology, Epistemology and Axiology.